Pemahaman E-Filling, Peran Pelayanan Account Representative dan Kualitas Teknologi Informasi terhadap Kepatuhan Wajib Pajak UMKM Kota Semarang - Yusranaditya, Rastia; Aresteria, Maya (BUDGETING : Journal of Business, Management and Accounting, 2024)
Taxpayer compliance is a behaviour of taxpayers in fulfilling their tax responsibilities in accordance with applicable tax laws and regulations. This study aims to analyse the effect of the comprehension of e-filing, role of account representatives services, and the quality of information technology on taxpayer compliance. The population in this study uses small and medium enterprise taxpayers in the Semarang City. The sampling method used in this study was carried out through simple random sampling, with a total sample of 100 respondents. Data collection was carried out through distributing questionnaires. The data analysis method used is a quantitative descriptive research method with processing data quality tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis tests. The results of this study indicate that the understanding of e-filing, the service role of account representatives, and the quality of information technology have a positive and significant effect on taxpayer compliance. Keywords: Comprehension Of E-Filing, Role Of Account Representative Services, Taxpayer Compliance, Quality Of Information Technology